Correlates of Compassion for Suffering Social Groups. Issue 4 (8th August 2022) - Floyd, Kory; Ray, Colter D.; James, Rebecca; Anderson, A. J.
ABSTRACT: This study investigates whether multiple factors correlate positively or inversely with compassion felt toward suffering social groups. Data were collected from 367 participants during April 2020 to investigate hypotheses in the context of three suffering social groups in the United States during that time: the Black American community, the LGBTQ community, and those directly affected by COVID-19. Results showed that compassion toward suffering groups covaries inversely with one's own ingroup preference. Compassion toward suffering social groups also covaried positively with the extent to which a person identifies with a suffering social group or knows people in a suffering social group. Additionally, loneliness was inversely correlated with compassion for suffering groups. These results suggest that although compassion is an important emotional motivator for engagement in prosocial behaviors that are vital to maintaining relationships, multiple factors can enhance or inhibit it.